Effects of a combination of bifidobacteria quadruple viable bacteria tablets and quadruple therapy on inflammatory response and Helicobacter pylori eradication rate in patients with Helicobacter pylori positive gastric ulcers - Jiang, Chunying; Shi, Jing; Zhuang, Xinfu; Zhou, Meng; Zhong, Haiyan (Frontiers in Medicine, 2025)
ObjectiveTo explore the effects of bifidobacteria quadruple viable bacteria tablets (Bifidobacterium infantis, Lactobacillus acidophilus, Enterococcus faecalis, and Bacillus cereus) plus quadruple therapy on inflammatory response and Helicobacter pylori (Hp) eradication rate in patients with Hp-positive gastric ulcers.MethodsOne hundred patients with Hp-positive gastric ulcers admitted in our hospital from January 2022 to December 2024 were included and divided into a control group and a study group. The former accepted quadruple therapy (esomeprazole magnesium enteric-coated capsules + colloidal bismuth pectin capsule + clarithromycin tablets + amoxicillin capsule). Based on the quadruple therapy, the latter was added with bifidobacteria quadruple viable bacteria tablets. The clinical symptoms, clinical efficacy, Hp eradication rate, levels of gastrointestinal hormones and inflammatory factors, immune function, number of beneficial bacteria, and incidence of adverse reactions were compared in both groups.ResultsFollowing 2 weeks of treatment, the study group had lower scores across these symptoms compared to the control group (P < 0.05). Furthermore, the study group had a higher total treatment efficacy rate and a higher Hp eradication rate compared to the control group (P < 0.05). Compared to the control group, the study group had higher levels of serum somatostatin and lower levels of motilin, gastrin, and pepsinogen I following 2 weeks of treatment (P < 0.05). Additionally, the study group had lower levels of interleukin-6 (IL-6), C-reactive protein (CRP), interleukin-8 (IL-8), and matrix metalloproteinase-9 (MMP-9) compared to the control group (P < 0.05). In comparison to the control group, the study group had higher levels of CD4 + T-cells, higher CD4 + /CD8 + ratio and lower CD8 + T-cell levels after 2 weeks of treatment (P < 0.05). Moreover, the study group had a significant increase in the abundance of beneficial gut microbiota, specifically Enterococcus faecalis, Lactobacillus acidophilus, and Bifidobacterium compared to the control group (P < 0.05). Lastly, the study group had a lower incidence of adverse reactions than the control group (P < 0.05).ConclusionBifidobacteria quadruple viable bacteria tablets plus quadruple therapy can improve the clinical symptoms, promote the clinical therapeutic effect and Hp eradication rate, improve the levels of gastrointestinal hormones and inflammatory factors, enhance the immune function, increase levels of beneficial bacteria and diminish the incidence of adverse reactions caused by quadruple therapy in patients suffered from Hp-positive gastric ulcer.